2021
DOI: 10.1108/lht-09-2021-0311
|View full text |Cite
|
Sign up to set email alerts
|

A worldwide quantitative review of the iSchools' archival education

Abstract: PurposeArchival studies have long been a critical part of information education around the world. This paper attempts to provide a worldwide overview of archival education among main information schools worldwide and find out their similarity and differences to suggest measures for the development of archival education.Design/methodology/approachQuantitative research is conducted including ten elements of the iSchools' archival education which are (1) geographical distribution, (2) names of degrees, (3) names … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…This article also highlights the impact of contemporary technology on LIS curricula. Readers may also be interested in reading about similar trends in archival studies programs recently published (Ng et al , 2022; Li and Chiu, 2022).…”
Section: Information Literacy Of Library and Information Science Prof...mentioning
confidence: 99%
“…This article also highlights the impact of contemporary technology on LIS curricula. Readers may also be interested in reading about similar trends in archival studies programs recently published (Ng et al , 2022; Li and Chiu, 2022).…”
Section: Information Literacy Of Library and Information Science Prof...mentioning
confidence: 99%
“…As new courses integrating information technology are introduced into LIS programs, competition has increased not only amongst LIS programs, but also amongst other departments within the same institution, especially when cross-disciplinary skills and topics such as digital humanities, marketing, knowledge management, web design and database management become expected of LIS graduates looking for employment (Markey, 2004;Moazeni, 2015;Ng et al, 2021;Li and Chiu, 2021). Although today's LIS programs have vastly been changed and such trends will continue, what constitutes current accredited programs or how accredited programs from different regions of the world differ from one another remains unclear (Tam et al, 2007).…”
Section: Ala and Clip Lis Program Review 1721mentioning
confidence: 99%
“…As such, this review addresses such issues by performing a quantitative comparison of the accredited programs in two of the world's leading LIS accreditation bodies, the American Library Association (ALA) and the Chartered Institute of Library and Information Professionals (CILIP). Program and curriculum information openly accessible through the websites of the accredited institutions were extracted and processed using a combination of methods referenced from past research to ensure results are comparable and to contribute to the literature of LIS curricula (Hall, 2009; Markey, 2004; Yi and Turner, 2014; Li and Chiu, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They summarized the findings into five themes to better interpret the meanings behind them. Li and Chiu (2022) reviewed iSchools' archival education system based on ten elements. They suggested that iSchools may explore the possibility of organizing more conferences and forums to exchange ideas on archival studies and education issues, which can attract more members worldwide and cooperate with other accreditation organizations of archival education.…”
Section: Faculty Research Characteristics and Information-seeking Beh...mentioning
confidence: 99%